Highly stereloselective synthesis of 2,5-disubstituted 3-vinylidene tetetrahydrofurans via Prins-type cyclization - Shin, C; Chavre, SN; Pae, AN; Cha, JH; Koh, HY; Chang, MH; Choi, JH; Cho, YS (AMER CHEMICAL SOC, 2005)
A novel synthetic methodology for 2,5-disubstituted tetrahydrofurans having an allenyl group at the 3-position via Prins-type cyclization was developed. The reaction led to excellent selectivity and moderate to high yields.
Keywords: DIASTEREOSELECTIVE SYNTHESIS; TRANS-2,5-DISUBSTITUTED TETRAHYDROFURANS; STEREOSELECTIVE-SYNTHESIS; MEDIATED CYCLIZATIONS; CONVENIENT SYNTHESIS; TETRAHYDROPYRANS; ETHERS; CARBINOLS; EPOXIDES; ALCOHOLS